Effectiveness of Hedon (Heel Donut) as an Effort to Prevent Pressure Ulcers on the Calcaneal of Tractioned Patients - Rahmasari, Ikrima; Utomo, Endrat Kartiko; Ridzuan, Ilyas Syafiq Darul; Sukini, Sukini (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Fracture is a condition where the continuity of bone tissue and/or cartilage is completely or partially broken, caused by force trauma or osteoporosis. Fracture management includes conservative measures and surgical procedures. Conservative measures given include plaster casts, splints, skin traction, bone traction, as well as repairs by manipulation and repositioning to a position close to normal. One of the impacts of installing skeletal traction is pressure ulcers. Pressure ulcers are a problem that often occurs in prominent bony areas such as the heel (calcaneal). Objective: patients who are installed in skeletal traction. Method: using pre-experimental methods with One-group pre-post test design techniques. Results: Based on the occurrence of pressure ulcers before being given the heel donut, there were 8 patients who did not experience pressure ulcers with a percentage of 57.1% and 6 patients who experienced stage 1 pressure ulcers, 42.8%. After being given the heel donut, 14 patients did not experience pressure ulcers with a percentage of 100% and no respondents experienced stage 1 pressure ulcers after being given the heel donut. Conclusions: Hedon (heel donut) is effective in preventing pressure ulcers in the calcaneal of patients who are installed in skeletal traction.